2003
DOI: 10.1291/hypres.26.97
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Inhibitory Effects of Y-27632, a Rho Kinase Inhibitor, in Strips of Small and Large Mesenteric Arteries from Spontaneously Hypertensive and Normotensive Wistar-Kyoto Rats.

Abstract: Since Y-27632, a specific inhibitor of Rho kinase, decreases the blood pressure in spontaneously hypertensive rats (SHR), it is suggested that Rho kinase is involved in the pathophysiology of hypertension. However, the effects of Y-27632 on isolated resistance arteries have never been determined. This study aimed to examine the possible role of the Rho/Rho kinase pathway during arterial contraction in isolated resistance arteries from SHR. The profile of arterial relaxant effects of Y-27632 was compared in end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 32 publications
3
28
1
1
Order By: Relevance
“…The role of rho-kinase in mediating contractile responses has been studied extensively (Bolz et al, 2000;Matrougui et al, 2001;Budzyn et al, 2006;Faraci et al, 2006). However, to the best of our knowledge, only one previous study has compared how the contribution of rho-kinase to contractile responses might vary between functionally distinct arteries within a vascular bed (Asano and Nomura, 2003). We found evidence for a role of rho-kinase in contractile responses to phenylephrine in both aorta and SMA, albeit to varying degrees.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The role of rho-kinase in mediating contractile responses has been studied extensively (Bolz et al, 2000;Matrougui et al, 2001;Budzyn et al, 2006;Faraci et al, 2006). However, to the best of our knowledge, only one previous study has compared how the contribution of rho-kinase to contractile responses might vary between functionally distinct arteries within a vascular bed (Asano and Nomura, 2003). We found evidence for a role of rho-kinase in contractile responses to phenylephrine in both aorta and SMA, albeit to varying degrees.…”
Section: Discussionmentioning
confidence: 74%
“…Importantly, rho-kinase inhibition had no effect on contractile responses of BMA to all three contractile agents. Thus, in general, it seems that rho-kinase has a major role in mediating contractile responses of larger conductance vessels, whereas its contribution is greatly diminished in small resistance vessels (Asano and Nomura, 2003).…”
Section: Discussionmentioning
confidence: 97%
“…causes relaxation in large and small vessels (Asano and Nomura, 2003). These two pathways, PI3-kinase and Rho/Rhokinase, may be interconnected and the nature of this interaction in spontaneous tone in aorta from DOCA-salt rats was the goal of the present study.…”
Section: Discussionmentioning
confidence: 97%
“…14 -24 Using Y-27632 to inhibit Rho-kinase, Uehata et al 14 as well as others [15][16][17][18][19][20][21][22][23] have demonstrated a role for Rho-kinase specific to receptormeditated contraction. Additionally, they were the first to demonstrate a role for RhoA and Rho-kinase in various animal models of hypertension.…”
Section: Increased Vasoconstriction and Rhoa/rho-kinase Signaling In mentioning
confidence: 99%
“…Asano and Nomura 16 compared the inhibitory effects of Y-27632 on contractile responses in small and large mesenteric arteries from SHR and normotensive rats. The arteries were contracted to a plateau phase with norepinephrine and subsequently treated with the Rho-kinase inhibitor.…”
Section: Increased Vasoconstriction and Rhoa/rho-kinase Signaling In mentioning
confidence: 99%